2014
DOI: 10.1155/2014/628505
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Carbon Steel in Synthetically Produced Oil Field Seawater

Abstract: The life of offshore steel structure in the oil production units is decided by the huge corrosive degradation due to SO42-, S2−, and Cl−, which normally present in the oil field seawater. Variation in pH and temperature further adds to the rate of degradation on steel. Corrosion behavior of mild steel is investigated through polarization, EIS, XRD, and optical and SEM microscopy. The effect of all 3 species is huge material degradation with FeSx and FeCl3 and their complex as corrosion products. EIS data m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Generally, for all S, the corrosion rate (CR) increased with increasing temperature. This is in line with the model of corrosion rate controlled by chemical reactions and oxygen diffusion (Melchers's phases 0 and 1) [61]. In addition, it was found that the CR at non-standard salinity levels was considerably higher, than at S 35.…”
Section: Eis Spectroscopysupporting
confidence: 86%
“…Generally, for all S, the corrosion rate (CR) increased with increasing temperature. This is in line with the model of corrosion rate controlled by chemical reactions and oxygen diffusion (Melchers's phases 0 and 1) [61]. In addition, it was found that the CR at non-standard salinity levels was considerably higher, than at S 35.…”
Section: Eis Spectroscopysupporting
confidence: 86%